Kebijakan Penegerian Satuan Pendidikan Keagamaan Kristen di NTT: Upaya Pemerataan Akses Pendidikan di Daerah Tertinggal - Henukh, Greybin (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper describes that problem of education in East Nusa Tenggara (NTT) is still dominated by access inequality, especially in underdeveloped areas, exacerbated by infrastructure limitations, geographical constraints, and a shortage of qualified teachers. Although private Christian Religious Education Units (SPKK) have been the backbone, resource limitations hinder their performance, widening educational disparities. This study uses a qualitative-exploratory approach with literature reviews and government reports, as well as descriptive-qualitative analysis. The results show that the policy of nationalizing SPKK, stipulated in Ministerial Regulation of Religious Affairs (PMA) Number 23 Year 2024, has brought fresh air, but faces significant challenges such as limited supporting documents (especially land certificates), lack of land, and limited budget and welfare of educators. The disparity between the number of nationalized SPKK (4) and nationalized madrasahs (73) in NTT also indicates an imbalance in government support. The development of Christian religious education in underdeveloped areas of NTT requires a holistic and adaptive strategy that integrates the nationalization policy with strengthening accessibility, infrastructure, improving teacher welfare, simplifying the nationalization process, preserving religious identity post-nationalization, and strengthening data accountability. The conclusion of this study affirms that the nationalization policy is a correct step, but its implementation in NTT still faces complex obstacles that require more adaptive, flexible, and collaborative policy adjustments. The main policy recommendations are to develop adaptive and needs-based SPKK Nationalization Guidelines, ensure strategic partnerships with churches/foundations, and accelerate SPKK access to government support.